PENGARUH PERSONAL KNOWLEDGE, JOB PROCEDURE DAN TEKNOLOGI TERHADAP KINERJA KARYAWAN (Studi Kasus Penerapan Knowledge Management pada PT. Nasmoco Karangjati Motor) - Puji Susanti Lestari; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2017)
This research is motivated by globalization and the rapid development of science as a source of the driving force of the organization, so that it becomes competitive organization and competitiveness. Development organizations, both businesses and public organizations to improve the competitiveness of a competitive, rife with using the knowledge asset approach. A change of leadership of the new branch of PT. New Ratna Motor since 2016 so there is a change related to the company's policy is applied, this affects the performance of employees for necessary adjustments to the new policy. The objective of this study was to determine the effect of personal knowledge, job procedures and technology to employee performance. This type of research is explanatory research with data collection through interviews and questionnaires. The sampling technique using census sampling techniques or saturated. Samples in this study amounted to 57 respondents who are permanent employees and contract employees of PT. Nasmoco Karangjati Motor. This study uses qualitative and quantitative analysis techniques. Quantitative analysis using validity, reliability, coefficient correlation, simple and multiple regression analysis, the coefficient of determination and significance test t test and F. Based on the results of simple linear regression analysis, found that the variable of personal knowledge, job procedures and technology affect the performance of employees with a coefficient of 4.852; 5.341; and 7.274. Simultaneously, variable personal knowledge, job procedures and technology affect the performance of employees with F count> F table (21.036> 2.773) with a significant number 0.0000 <0.05. The conclusion of this study is the personal knowledge and significant positive effect on the performance of employees of PT. Nasmoco Karangjati Motor. Job procedure positive and significant effect on the performance of employees of PT. Nasmoco Karangjati Motor. Technology positive and significant effect on the performance of employees of PT. Nasmoco Karangjati Motor. The dominant variable affecting the performance of technology, this is because every division uses technology to simplify the task menjalanakan. Advice can be given by researchers to the company that the expected to updated periodically appropriate technology systems business development for technology variables most dominating performance of employees. Companies should be firm to the employees that they came too late to be more disciplined. The management needs to set up a schedule of training for new employees in order to reduce employee absence in the training. Socialization and motivation to employees the importance of responsibility and a sense of ownership of the company, a solid loyalty can make employees become personally responsible for adhering to the commitments.